Unlocking the Potential of Enterprise Structured Waqf for Business Based Pesantren in Indonesia - Iskandar; Husni Mubarrak; Arroyyan Ramly (Proceeding of International Conference on Islamic Boarding School, 2025)
Pesantren, as Islamic educational institutions, play a crucial role in shaping religious and moral values in Indonesia. In addition to their educational function, many pesantren have developed business units to sustain their operational costs. However, challenges such as financial sustainability, limited managerial expertise, and regulatory constraints often hinder their ability to achieve economic independence. This study examines the potential of implementing the Enterprise-Structured Waqf (ESW) model as an innovative approach to strengthen the economic foundations of business-based pesantren in Indonesia. The ESW model is a waqf-based corporate model that integrates the principles of Islamic endowment (waqf) with modern business management. This model allows waqf assets to be managed professionally, generating sustainable revenues while maintaining the original waqf objectives. This research employs a qualitative approach, utilizing content analysis of existing literature, including academic journals, books, policy papers, and case studies on enterprise waqf models. The findings of this study suggest that ESW has strong potential to be implemented in Indonesian pesantren, offering a sustainable solution for enhancing their financial autonomy. By leveraging waqf assets for productive economic activities, pesantren can generate long-term revenue streams while fulfilling their social and educational missions. However, several challenges need to be addressed, including low waqf literacy, legal ambiguities, and the need for capacity building among pesantren stakeholders. This study recommends targeted policy support, increased collaboration with Islamic financial institutions, and tailored training programs to facilitate the adoption of the ESW model in pesantren across Indonesia.